Designing a competency model for the succession of nursing managers, using the Fuzzy Inference System - Marzieh Khorasani-Gerdehkouhi; Seyed Mahmoud Taheri; Mohammad Ali Cheraghi (Nursing Practice Today)
Background & Aim: Identifying competencies is fundamental for effective succession planning. Studies show that achieving a suitable succession planning model for mid-level nursing managers/supervisors can be helpful in achieving the desired goals of top-level nursing managers/matrons. Thus, this study aimed to design a competency model for the succession of mid-level nursing managers from the perspective of top-level nursing managers using the Fuzzy Inference System. Methods & Materials: This health services management research was conducted during 2020-2021. Participants in this study included top-level nursing managers/matrons working in the hospitals affiliated with the Tehran University of Medical Sciences. A census sampling method was used in this study with 14 matrons participating as experts. A three-level Fuzzy Inference System was designed by a competency model for mid-level nursing managers/supervisors, using the previous study. Input and output variables were defined, and fuzzy questionnaires were designed using pair-wise comparison matrices to gather expert opinions on fuzzy rules. These rules were analyzed using MATLAB (R 2019 b) software to compare the effect of each criterion on other levels. Results: The results showed that managerial experience, equipment management, emotional intelligence, influence and impact on others, self-confidence, and strategic thinking in the first Fuzzy Inference System level, as well as management abilities, influencing skills, and leading management development in the second level, were more influential. In the third- level, the perceptual, relational, and technical variables had higher priorities, respectively. Conclusion: Senior managers could use the proposed model as a checklist/questionnaire to make strategic planning for the succession of nursing managers.